Bcl-2 and FKBP12 bind to IP3 and ryanodine receptors at overlapping sites: the complexity of protein–protein interactions for channel regulation. (1st June 2015) - Vervliet, Tim; Parys, Jan B.; Bultynck, Geert
Abstract : The 12- and 12.6-kDa FK506-binding proteins, FKBP12 (12-kDa FK506-binding protein) and FKBP12.6 (12.6-kDa FK506-binding protein), have been implicated in the binding to and the regulation of ryanodine receptors (RyRs) and inositol 1, 4, 5-trisphosphate receptors (IP3 Rs), both tetrameric intracellular Ca 2+ -release channels. Whereas the amino acid sequences responsible for FKBP12 binding to RyRs are conserved in IP3 Rs, FKBP12 binding to IP3 Rs has been questioned and could not be observed in various experimental models. Nevertheless, conservation of these residues in the different IP3 R isoforms and during evolution suggested that they could harbour an important regulatory site critical for IP3 R-channel function. Recently, it has become clear that in IP3 Rs, this site was targeted by B-cell lymphoma 2 (Bcl-2) via its Bcl-2 homology (BH)4 domain, thereby dampening IP3 R-mediated Ca 2+ flux and preventing pro-apoptotic Ca 2+ signalling. Furthermore, vice versa, the presence of the corresponding site in RyRs implied that Bcl-2 proteins could associate with and regulate RyR channels. Recently, the existence of endogenous RyR–Bcl-2 complexes has been identified in primary hippocampal neurons. Like for IP3 Rs, binding of Bcl-2 to RyRs also involved its BH4 domain and suppressed RyR-mediated Ca 2+ release. We therefore propose that the originally identified FKBP12-binding site in IP3 Rs is a region critical for controlling IP3 R-mediated Ca 2+ flux by recruiting Bcl-2 rather than FKBP12. Although we hypothesize that anti-apoptotic Bcl-2 proteins, but not FKBP12, are the main physiological inhibitors of IP3 Rs, we cannot exclude that Bcl-2 could help engaging FKBP12 (or other FKBP isoforms) to the IP3 R, potentially via calcineurin.